End-systolic wall stress in aortic stenosis: comparing symptomatic and asymptomatic patients - Redi Pecini; Jacob Eifer Moller; Rasmus Carter-Storch; Nicolaj Lyhne Christensen; Lars Melholt Rasmussen; Eva Søndergård; Lars Melgaard Videbæk; Jordi Sanchez Dahl (Open Heart)
Aims In aortic stenosis (AS), there is poor association between symptoms and conventional markers of AS severity or left ventricular (LV) systolic function. This may reflect that symptoms arise from LV diastolic dysfunction or that aortic valve area (AVA) and transvalvular gradient do not reflect afterload. We aimed to study the impact of afterload (end-systolic wall stress [ESWS]) on the presence of symptoms in AS and to test whether symptoms are related to increased ESWS or LV remodelling.Methods and results In a prospective study, ESWS was estimated by measuring LV wall thickness from MRI and estimated LV end systolic pressure from echocardiographic mean gradient and systolic blood pressure in 78 patients with severe AS scheduled for aortic valve replacement and 91 patients with asymptomatic severe AS. Symptomatic patients had lower indexed AVA (0.40±0.11 vs 0.45±0.09 cm2/m2, p=0.009). They had undergone more extensive remodelling (MRI LV mass index [LVMi]: 85±24 vs 69±17 g/m2, p<0.0001), had higher tricuspid regurgitant gradient (24±8 mm Hg vs 19 ± 7 mm Hg, p=0.0001) and poorer global longitudinal strain (−15.6±3.8 vs −19.9±3.2%, p<0.0001). ESWS was higher among symptomatic patients (96±51 vs 76±25 kdynes/cm2, p=0.003). Multivariate logistic regression identified echocardiographic relative wall thickness, tricuspid gradient, mitral deceleration time, early diastolic strain rate, MRI LVMi, MRI LV end-diastolic volume index and ESWS as independently associated with being symptomatic.Conclusion ESWS can be estimated from multimodality imaging combining MRI and echocardiography. It is correlated with LV remodelling and neurohormonal activation and is independently associated with symptomatic status in AS.